Pain, Pressure Pain Threshold and Disability Following One Session of Dry Needling in Subjects with Active Trigger Points in the Upper Trapezius Muscle - Reza Ebrahimi; Navid Taheri (Vesnu Publications, 2016)
Introduction: Myofascial pain syndrome is a common, non-articular musculoskeletal disorder characterized by local tenderness and referral pain due to the active trigger points in muscles. The aim of this study was to evaluate the effects of one session of dry needling in subjects with active trigger points in upper trapezius muscle. Materials and Methods: 23 subjects with active trigger points in upper trapezius muscle participated in the study. The pain intensity and Disability Index were measured using visual analogue scale (VAS) and Neck Disability Index questionnaire, respectively. All data were measured before and one week after the intervention. Using algometry, the pressure pain threshold was also measured immediately after the dry needling. Results: There were significant differences in mean pressure pain threshold among the three measurements (P < 0.001). The pressure pain threshold significantly decreased immediately after the intervention (P = 0.001); although it significantly increased a week later compared to before the intervention (P = 0.001). There was significant decrement in the mean Disability Index score and pain intensity after the intervention (P < 0.001). Conclusion: One week after one session of dry needling, disability, pain intensity and pressure pain threshold improved considerably in subjects suffering from active trigger points in upper trapezius muscle.